DOMINATION PARAMETERS OF POWER OF CENTIPEDE AND PN + KM - Prasad, G. Easwara (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
The domination parameters of a graph of order has been already introduced. It is defined as is a dominating set of if every vertex is adjacent to atleast one vertex in In this paper, we have established various domination parameters of power of Centipede graph and Pn + Km , also we have studied the relation between this parameters and illustrated with an examples. Keywords: Graph, Domination, Centipede, Path and null graph